Underspecified Focus Representation - Schröder, Bernhard; Schmitz, Hans-Christian (Proceedings of the Amsterdam Colloquium, 2003)
Sentences involving more than one focus are quite common in natural language. Multiple focus constructions can be ambiguous with respect to the association of focuses and focus operators. We show how this form of ambiguity can be handled alongside with scope ambiguity within the framework of Minimal Recursion Semantics. We start from the ideas of Structured Meaning Theory for focus constructions and show how this theory can be extended such that it handles focus associations not handled by the original form of the theory, it allows for various degrees of underspecification and it is compositionally implemented in HPSG.